Performance of Broilers Fed Diets Supplemented with a Phytogenic Mixture as an Alternative of Antibiotic Growth Promoters - Singh, Vikash Vikram; Singh, Vijay Kumar; Tewari, Dharmesh; Gautam, Sachin; Singh, Virendra Bahadur; Singh, Prateek (Indian Journal of Animal Nutrition, 2019)
In order to evaluate the effect of a phytogenic mixture on the performance of broiler chickens two hundred fifty Vencobb-400Y strain day old broiler chicks were randomly divided into five groups randomly and kept either on basal diet without any supplement (NCON), basal diet + antibiotic (PCON), basal diet + 1% phytogenic mixture (LPH), basal diet + 2% phytogenic mixture (MPH) and basal diet + 3% phytogenic mixture (HPH) for 35 days. The phytogenic mixture supplemented group’s birds had higher body weight than the control group birds and the mean body weight of LPH, MPH and HPH was significantly (P<0.05) higher than NCON group.After 35 days of experimental period it was found that the total feed intake of phytogenic supplemented birds were similar to NCON but higher to PCON birds. Among the phytogenic mixture supplemented birds, lowest feed intake was observed in MPH group. Among the herbal supplemented groups, lowest FCR was found in MPH group and it was similar to PCON group. The EER of herbs supplemented birds were significantly (P<0.05) higher than NCON and lower to PCON group birds. The PER of phytogenic mixture supplemented birds were significantly (P<0.05) higher than NCON and lower than PCON group birds. Among herbal groups the highest PER was found in MPH group. The phytogenic mixture supplemented birds performance index were significantly (P<0.05) better in comparison to NCON birds. The economic efficiency and relative economic efficiency data revealed that rearing of broilers on phytogenic mixture was more economical than NCON but less economical than the birds reared on conventional system of rearing i.e. on AGP. The results suggest that 2% phytogenic mixture was economical and had potential to use as an alternative of AGP in broiler rearing.